An analysis of teacher knowledge for teaching functional thinking to elementary school students. Issue 3 (September 2022) - Pang, JeongSuk; Sunwoo, Jin
Given the significance of functional thinking at the elementary school level, there has been growing interest in teachers who play a major role in enhancing students' functional thinking. This study surveyed 119 elementary school teachers in Korea to investigate their knowledge for teaching functional thinking. A written assessment was developed for this study regarding the knowledge of mathematical tasks, instructional strategies, and mathematical discourse to teach functional thinking. The results of this study showed that many teachers could design mathematical tasks corresponding to simple relationships of two quantities but some of them had difficulties in constructing the task fory = 2 x + 2 . Teachers could explain the affordances of key instructional strategies to foster functional thinking and identify students' typical errors in recognizing or representing a functional relationship but some explanations included a superficial understanding of the core ideas of functional thinking. Based on these results this article closes with a discussion of several implications regarding the aspects needed for elementary school teachers to further promote students' functional thinking.